An integrative study of the implications of the rise of coworking spaces in smart cities - Zhao, Fang (2020)
Coworking practices have proliferated around the world being embraced not only by remote workers, start-up employees and freelancers but also by larger organizations. coworking spaces in public libraries, business districts and other urban spaces, herald profound changes for the way workspaces are used in cities. The study takes an integrative approach to investigate the economic and socio-cultural implications of coworking trend for smart cities, their ecosystems and the use of urban public spaces. The study examines these issues by studying motivations and challenges of providers and users of coworking spaces. Thirty coworking spaces in urban areas across Australia were studied and thirty-four semi-structured interviews were conducted with both providers and users of the coworking spaces. The findings suggest that coworking spaces play an important role in building communities and developing social and cultural ties. From urban space and environmental perspectives, coworking spaces are likely to contribute to urban mobility and sustainability. From an urban economic perspective, coworking spaces provide a collaborative environment and often a breeding ground for entrepreneurship. Entrepreneurship is one of the most salient themes in the coworking spaces as found in this study. These findings will inform urban policy makers and help them better understand and tap into the source of civic entrepreneurship derived from coworking spaces.